A Comparison between The Effectiveness of Short Message Service and Reminder Cards Regarding Medication Adherence in Patients with Hypertension: A Randomized Controlled Clinical Trial - Masumeh Hemmati Maslakpak; Mahsa Safaie (Shiraz University of Medical Sciences, 2016)
Background: Hypertension is increasing rapidly in developing countries. Today, modern technologies are suggested as the tools used to enhance medication adherence. This study aimed to compare the effectiveness of short message service (SMS) to reminder cards with regard to medication adherence in patients with hypertension. Methods: The present study is a randomized controlled clinical trial. The subjects consisted of 123 patients with hypertension at the clinical-educational center of Sayyed-Al Shohada, Urmia, who met the study criteria. Selected based on the convenience method, the samples were randomly divided into three groups: the SMS group, the reminder-cards group, and the control group. The subjects in the SMS group were sent 6 text messages a week for three months, and the subjects in the reminder-cards group were trained in how and in what order to use their cards. Hill-Bone medication adherence scale was completed by all the participants before and three months after the intervention. Data analysis was performed in SPSS software, using one-way ANOVA. Hill-Bone medication adherence scale was completed by all the participants before and three months after the intervention. Data analysis was performed in SPSS software, using one-way ANOVA. Results: The results of ANOVA test demonstrated that the mean scores of medication adherence were statistically different among the three groups of control (46.63±2.99), SMS (57.70±2.75) and the reminder cards (57.51±2.69) after the intervention (P<0.001). However, after the intervention the means of the patients' medication adherence scores were not statistically different between the two groups trained via SMS and reminder cards (P>0.05). Conclusion: The findings of the present research demonstrated that training and distance-monitoring via SMS and reminder cards promote medication adherence of patients. Therefore, healthcare teams and nurses are recommended to apply such training methods.